Requirements engineering: A systematic mapping study in agile software development - Curcio, Karina; Navarro, Tiago; Malucelli, Andreia; Reinehr, Sheila (The Journal of systems and software, 2018)
•SCRUM picture was replaced.•Requirements modification statement was revised.•References format was corrected. Requirements engineering in agile software development is a relatively recent software engineering topic and it is not completely explored and understood. The understanding of how this process works on agile world needs a deeper analysis. The goal of this paper is to map the subject area of requirements engineering in agile context to identify the main topics that have been researched and to identify gaps to develop future researches. It is also intended to identify the obstacles that practitioners face when using agile requirements engineering. A systematic mapping study was conducted and as a result 2171 papers were initially identified and further narrowed to 104 by applying exclusion criteria and analysis. After completing the classification and the analysis of the selected studies it was possible to identify 15 areas (13 based on SWEBOK) where researches were developed. Five of such areas points to the need of future researches, among them are requirements elicitation, change management, measuring requirements, software requirements tools and comparative studies between traditional and agile requirements. In this research, some obstacles that practitioners face dealing with requirements engineering in agile context were also identified. They are related to environment, people and resources.